A-153 Characteristics of Patients Seeking Treatment for "Brain Fog" Secondary to Post-Acute Sequelae of COVID-19 (PASC) in the Deep South. (17th August 2022) - Robinson, Jamie Hansel; Greenfield, Melissa J; Lokken, Kristine; Shah, Udit Vipul; Agnihotri, Shruti P; Wheeler, Pariya Fazeli; Vance, David E; Kennedy, Richard; Gerstenecker, Adam; Lazar, Ronald M; Martin, Roy C; Gerstenecker, Kristen Triebel
Abstract: Objective: Describe those with persistent neuropsychiatric symptoms seeking treatment for Post-Acute Sequelae of COVID-19 (PASC). Method: Patients were referred for neuropsychological evaluation from the University of Alabama at Birmingham (UAB) Post-COVID Treatment Program. Ninety-seven patients completed a comprehensive set of self-report questionnaires. Results: Patients were 49 years old (range: 18 to 74), had 15.49 years (SD = 2.43) of education, and identified as female (77%), married (51%), and White/Caucasian (73%) or Black/AA (25%). Reported annual income ranged from ≤ $20, 000 (11%) to ≥ $100, 000 (32%), with 75% currently employed. Confirmed positive test result for COVID-19 was reported in 88%, with 87% having the original virus and 13% the Delta variant, based on estimated dates of infection. Symptoms during the acute illness included: headache (76%), fever (51%), cough (57%), shortness of breath (56%), and loss of smell or taste (54%). Most of the participants were not hospitalized (76%) nor required oxygen therapy (78%). Persistent symptoms included: headache (55%), shortness of breath (53%), muscle and joint pain (53%), cough (17%), congestion (40%) and loss of smell or taste (25%). Of these participants, 87% reported they had not returned to their baseline health because of COVID-19 and most indicated impaired job performance following COVID-19 infection. Conclusion: Those who sought treatment for persistent neuropsychiatric symptoms following a symptomatic course of COVID-19 were commonly middle aged, White, women, with at least a high school education. "Brain fog" secondary to PASC can result in reported persistent health and neuropsychiatric issues that can impact ability to work.